An accurate and sensitive effervescence-assisted liquid phase microextraction method for the determination of cobalt after a Schiff base complexation by slotted quartz tube-flame atomic absorption spectrophotometry in urine samples - Borahan, Tulay; Zaman, Buse Tugba; Polat, Busra Sumeyye Arica; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2021)
In this study, an accurate analytical method development for cobalt determination in urine samples was described. The method is based on the mass transfer of the target analytes to the organic phase from the aqueous phase by the dispersing extractant throughout the solution with the aid of CO2 bubbles prior to sample measurement by using a slotted quartz tube flame atomic absorption spectrophotometer. An extractor (1-decanol) dropped effervescent tablet (anhydrous sodium carbonate and sodium dihydrogen phosphate dihydrate mixture) was used in order to separate/preconcentrate cobalt after complexation of cobalt ions in aqueous solution with the Schiff base ligand. The parameters affecting the extraction output such as complexing conditions (pH, ligand concentration, and volume) and extraction conditions (extraction solvent type and volume, extraction temperature, and heating duration, NaOH volume and mixing period) were optimized to lower the detection limit. The limit of detection and quantification values under optimized experimental and instrumental conditions were determined as 3.7 mu g L-1 and 12 mu g L-1, respectively with high linearity with respect to the dynamic range between 15 and 300 mu g L-1. The enhancement factor obtained with the developed method was calculated as 83 fold. The pretreatment process was applied to urine samples in order to test the convenience of the developed method in urine samples for the determination of cobalt at low levels. The high percentage recovery results of 96-97% for four different concentrations of spiked urine samples indicated the proposed method's sufficient sensitivity for analyte determination in such a complex matrix.
Keywords: Chemistry; Food Science & Technology; Spectroscopy